Persuasive Communication Style in the Qur'an: Analysis Based on the Stages of Revelation - Mursalim Mursalim (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This article examines the persuasive communication style in the Qur'an with an emphasis on the dynamics of the stages of revelation, especially in the context of the Makkiyah and Madaniyah periods. This research departs from the assumption that the Qur'an is not only a normative text, but also a divine communication medium that has a persuasion strategy that is adaptive to the social conditions of the ummah. Using a thematic interpretation approach (maudhu'i) and communication analysis, this study traces the patterns of persuasion used in Qur'anic verses, such as narratives, dialogues, parables, threats (tarhÄ«b), good news (targhÄ«b), and rational argumentation. Research shows that the Qur'an has a systematic and adaptive persuasive communication strategy, which is reflected in the integration of ethos, pathos, and logos elements. In the Makkiyah phase, the communication of the Qur'an tends to be emotional and spiritual, while in the Madaniyah phase it is more rational and normative. In addition, the concept of tadarruj shows that the Qur'an applies a gradual communication strategy in shaping social change. This research confirms that the Qur'an can be understood as a contextual and transformative model of persuasive communication, and contributes to the development of interdisciplinary Islamic communication studies.